1991
DOI: 10.1007/bf00371821
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the relative alkylation index (RAI) model for skin sensitization and application to mouse and guinea-pig test data for alkyl alkanesulphonates

Abstract: A derivation, more rigorous than hitherto, of the Relative Alkylation Index (RAI) as a quantifier of carrier protein haptenation in skin sensitization tests is presented. It is shown that the RAI, which is a composite parameter made up of dose, reactivity and lipophilicity terms, is likely to require a higher weighting for the reactivity term in the case of non-adjuvant tests than in the case of Freund's adjuvant-based tests. Methyl alkane-sulphonates, RSO3Me with R ranging from n-C6H13 to n-C16H33, were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…In a number of sensitization experiments 2-methoxy-6-alkyl-1,4-benxoquinones with branch side chain length C1-C15, including primin, have showed an increase of the sensitizing capacity with increasing length of the alkyl side chain from C-1 to C-13 (reaching maximum activity at an alkyl chain of 10 to 11 carbons), but the sensitizing potency decreased beyond 13 carbons and the sensitization hardly occurred at C-1 to C-3. Similar results were also obtained from studies on non-quinonoid compounds like catechols, phenols, hydroquinones, and gallates (Roberts et al, 1991;Konig et al, 1993;Hausen et al, 1995). In this study, all major compounds with branch side chains identified from the wild P. obconica in China were shown to be 1 or 2 carbons in length.…”
Section: Resultssupporting
confidence: 87%
“…In a number of sensitization experiments 2-methoxy-6-alkyl-1,4-benxoquinones with branch side chain length C1-C15, including primin, have showed an increase of the sensitizing capacity with increasing length of the alkyl side chain from C-1 to C-13 (reaching maximum activity at an alkyl chain of 10 to 11 carbons), but the sensitizing potency decreased beyond 13 carbons and the sensitization hardly occurred at C-1 to C-3. Similar results were also obtained from studies on non-quinonoid compounds like catechols, phenols, hydroquinones, and gallates (Roberts et al, 1991;Konig et al, 1993;Hausen et al, 1995). In this study, all major compounds with branch side chains identified from the wild P. obconica in China were shown to be 1 or 2 carbons in length.…”
Section: Resultssupporting
confidence: 87%
“…Basketter et al (12) observed an increase in sensitizing capacity with simple bromoalkanes: the maximum was reached at a side chain length of C 15 /C 16 , with a decrease in the response by further elongation of the side chain. Roberts et al (13) showed that alkyl alkanesulfonates are able to sensitize guinea pigs increasingly with an increase in the length of the alkyl chain from C 6 to C 12 and that the sensitizing potential decreased from C 12 to C 16 This study also found a similar correlation between alkyl chain length and sensitization as in the case of bromoalkanes, alkanesulfonates, quinones, phenols and catechols. From these results, we can conclude that an MA with a linear side chain has its maximum sensitizing capacity when the length of the side chain is C 8 to C 13 .…”
Section: Discussionsupporting
confidence: 59%
“…As a result, for each IPE pair u≠v, (6) Each IPE pair corresponds to one MDDM from which one molecular similarity eigenvector can be formed. Since there are totally 36 distinct combinations of the currently defined eight IPE types, 36 eigenvectors, that is measures of molecular similarity, can be obtained for each molecule α. Dissimilarity between molecules α and β is given by (7) Where i refers to the i th eigenvalue in the corresponding eigenvetor of a specific IPE pair.…”
Section: Universal 4d-fingerprintsmentioning
confidence: 99%